Peningkatan Efektivitas Jalur Transportasi Melalui Pembangunan Glass Ball Station (Stasiun Bola Kaca) Sebagai Pendukung Pemerataan Ekonomi Sekaligus Sebagai Ikon Wisata Baru Indonesia - Habib, Muhammad Alhada Fuadilah; Suryaputra, Michelle; Diniati, Bintis Ti'anatud (Yayasan Literasi Sains Indonesia, 2022)
Abstract Indonesia is an archipelagic country consisting of 18,306 islands and separated by sea and ocean boundaries. Transportation by sea and air to connect the islands is still considered ineffective. Based on the predictions made by the projection of Indonesia's population growth in 2020, it is known that there is an imbalance in the distribution of the population in Indonesia. The uneven distribution of the population is caused by uneven development and is still concentrated in big cities, especially on the island of Java. As a result, many people are urbanizing to big cities with the imagination of getting a better life. The increasingly congested city conditions have caused various problems, ranging from micro to macro scales. Poverty, unemployment, environmental pollution, and congestion often color people's lives in urban areas. Meanwhile, there are still many problems for people living in remote areas, ranging from the lack of development of facilities and infrastructure, the lack of human resource development, poor internet connection, and even the absence of electricity. This condition, of course, hinders the development of people living in remote areas. Based on this problem, we propose an idea that can help equalize development and improve the welfare of the Indonesian people. The idea is to build a giant train station in the middle of the Java Sea and Banda Sea (glass ball station) that can connect all regions of the archipelago, as well as a new tourist icon for the Indonesian people to attract tourists from abroad. With this development, the problem of social and economic inequality in the territory of Indonesia can be resolved and can bring equity to the progress and welfare of the nation, as well as become a new source of foreign exchange through the tourism sector.